Fatigue and Fluoride Corrosion on Streptococcus mutans Adherence to Titanium-Based Implant/Component Surfaces - Correa, Cassia Bellotto [UNESP]; Pires, Juliana Rico [UNESP]; Fernandes-Filho, Romeu Belon [UNESP]; Sartori, Rafael [UNESP]; Vaz, Luis Geraldo [UNESP] (Wiley-Blackwell, 2009)
Purpose: The influence of fatigue and the fluoride ion corrosion process on Streptococcus mutans adherence to commercially pure Titanium (Cp Ti) implant/component set surfaces were studied.Materials and Methods: Thirty Nobel implants and 30 Neodent implants were used. Each commercial brand was divided into three groups. Group A: control, Group B: sets submitted to fatigue (105 cycles, 15 Hz, 150 N), and Group C: sets submitted to fluoride (1500 ppm, pH 5.5) and fatigue, simulating a mean use of 5 years in the oral medium. Afterward, the sets were contaminated with standard strains of S. mutans (NTCC 1023) and analyzed by scanning electronic microscopy (SEM) and colony-forming unit counts (CFU/mL).Results: By SEM, bacterial adherence was verified only in group C in both brands. By CFU/mL counts, S. mutans was statistically higher in both brands in group C than in groups A and B (p < 0.05, ANOVA).Conclusion: The process of corrosion by fluoride ions on Cp Ti implant/component sets allowed greater S. mutans adherence than in the absence of corrosion and with the fatigue process in isolation.
Keywords: Fluoride; corrosion; dental implants; bacterial adhesion